The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1439-0531.2008.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cloned Miniature Pigs by Enucleation using the Spindle View System

Abstract: Porcine somatic cell nuclear transfer (NT) has been successfully performed, but its efficiency remains quite low. In this study, we improvised on the enucleation method to enhance the development of NT embryos. Initially, an experiment was performed to determine the location relationship between the metaphase plate and the first polar body, where the results showed that the metaphase plate may frequently be displaced during the varying period of maturation process. When the metaphase plates were removed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
1
19
1
Order By: Relevance
“…In general, due to rapid growth and the potential for multiple cell divisions, fetal fibroblasts have been commonly used as nuclear donors in pig embryo cloning. The blastocyst rates of pig embryos cloned with FFs are below the level of 20% [30][31][32]. These data are substantially in accordance with our data showing that 14.5% of embryos cloned with FFs developed to blastocysts.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In general, due to rapid growth and the potential for multiple cell divisions, fetal fibroblasts have been commonly used as nuclear donors in pig embryo cloning. The blastocyst rates of pig embryos cloned with FFs are below the level of 20% [30][31][32]. These data are substantially in accordance with our data showing that 14.5% of embryos cloned with FFs developed to blastocysts.…”
supporting
confidence: 92%
“…The usefulness of miniature pigs as an animal model has been proven; but nevertheless, only a limited number of studies have reported on cloned miniature pigs derived from somatic donor cells [30,31,[34][35][36]. Because of the comparison with domestic pigs, production of cloned miniature pigs using miniature pigs oocytes has limitations.…”
Section: Lee Et Al 260mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach results in an enucleation rate that varies widely among laboratories (40%-90%) depending on the skill and experience of the operators; it is usually difficult to reach a high enucleation rate due to "blind" localization of the nucleus [2][3][4][5] . To increase enucleation efficiency, spindle imaging system-assisted (SIS-A) enucleation has been used for oocyte enucleation in pig, cattle and other species [6][7][8][9][10][11][12][13] . This method employs a polarized light microscope to visualize the meiotic spindle-containing oocyte nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…This method employs a polarized light microscope to visualize the meiotic spindle-containing oocyte nucleus. The SIS-A approach can achieve a high oocyte enucleation rate (88%-100%) in several mammalian species [8,10,12,13] and improve the in vitro development efficiency of cloned embryos in pigs and cattle [6,7] . Fluorescence dye staining has also been used to localize clearly the oocyte nucleus before enucleation [14,15] .…”
Section: Introductionmentioning
confidence: 99%